Hellwalkers - Smith, Alexander Gordon, 1979- (Smith, Alexander Gordon, 1979- Devil's engine., 2017)
After Marlow makes a deal with the Devil to get himself and Pan released from Hell, war breaks out and the friends have only each other, and hope, to combat demonic creatures and monsters.